Bioconversion of Shrimp By-Product into Carotenoids Using Pigmented Yeast Sporidiobolus Pararoseus QBioconversion of Shrimp By-Product into Carotenoids Using Pigmented Yeast Sporidiobolus Pararoseus Q - Nghiem, Hoang Lan; To, Kim Anh; Pham, Tuan Anh (JST: Engineering And Technology For Sustainable Development, 2024)
Chitin, a natural polysaccharide, is the second most abundant biopolymer in the world after cellulose. It consists of N-acetylglucosamine (NAG) monomers and finds widespread applications in the food, cosmetics, and pharmaceutical industries. In this study, we selected pigmented yeast strains to synthesize carotenoids from NAG and optimized the conditions for carotenoid production. The results demonstrated that the selected strain Sporidiobolus pararoseus Q could accumulate β-carotene and carotenoids, reaching 518.84 µg/g dry biomass and 595.48 µg/g dry biomass, respectively, after 96 hours of fermentation with 30 g/L NAG at pH 5. The two-step fermentation first with 80 g/L of glucose and then 50 g/L of NAG increased the carotenoids and ²-carotene yields by 41% and 35%, achieving 786.69 µg/g and 632.19 µg/g, respectively. The ability to use NAG as the feedstock for carotenoid production not only adds value to shrimp by-products but also contributes to controlling environmental pollution